Cross-kingdom regulation by dietary plant miRNAs: an evidence-based review with recent updates. Issue 20 (1st September 2021) - Jia, MingXi; He, JinTao; Bai, WeiDong; Lin, QinLu; Deng, Jing; Li, Wen; Bai, Jie; Fu, Da; Ma, YuShui; Ren, JiaLi; Xiong, ShouYao
Abstract : This study summarizes the mechanism by which plant-derived miRNAs remain stable and are absorbed in mammals, and reviews the updated evidence regarding the therapeutic potential of plant miRNAs' cross-kingdom activity. Abstract : As non-coding RNA molecules, microRNAs (miRNAs) are widely known for their critical role in gene regulation. Recent studies have shown that plant miRNAs obtained through dietary oral administration can survive in the gastrointestinal (GI) tract, enter the circulatory system and regulate endogenous mRNAs. Diet-derived plant miRNAs have 2′- O -methylated modified 3′ends and high cytosine and guanine (GC) content, as well as exosomal packaging, which gives them high stability even in the harsh environment of the digestive system and circulatory system. The latest evidence shows that dietary plant miRNAs can not only be absorbed in the intestine, but also be absorbed and packaged by gastric epithelial cells and then secreted into the circulatory system. Alternatively, these biologically active plant-derived miRNAs may also affect the health of the host by affecting the function of the microbiome, while not need to be taken into the host's circulatory system and transferred to remote tissues. This cross-kingdom regulation of miRNAs gives us hope for exploring their therapeutic potential and as dietary supplements. However, doubts have also been raised about the cross-border regulation of miRNAs, suggesting that technical flaws in the experiments may have led to this hypothesis. In this article, we summarize the visibility of dietary plant miRNAs in the development of human health and recent research data on their use in therapeutics. The regulation of plant miRNAs across kingdoms is a novel concept. Continued efforts in this area will broaden our understanding of the biological role of plant miRNAs and will open the way for the development of new approaches to prevent or treat human diseases.